New clinical technique for fabrication immediate partial denture - Abdulsalam Ali Zwiad (Wolters Kluwer Medknow Publications, 2013)
Immediate partial denture is a choice of treatment due to various cases of teeth extraction such as badly carious teeth, periodontal disease, eruption problems, trauma, and other reasons. Many choices are used to replace the lost teeth; one of these choices is a removable plastic denture in which hot cured acrylic resin should be used to fabricate such denture. Aim of Study: To provide an applicable technique to fabricate an immediate partial denture by reducing and declining the prosthetic steps and some materials in proportional to the conventional method. Clinical Procedures: Maxillary and mandibular stone casts are mounted to a simple articulator and the procedures are explained as step by step to fabricate an immediate partial denture without using the conventional methods and material, just using a small quantity of white cold cure acrylic resin to fabricate the artificial teeth, hot cure acrylic resin for the denture base and mold made of a silicon impression material are used to fabricate an immediate partial denture. Conclusion: The finished immediate partial denture showed a good retention and produced the exact shapes and sizes of the extracted teeth with low cost and less time for a dentist and patient.